If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 3 = 5(2x + -5) Reorder the terms: 3 + X = 5(2x + -5) Reorder the terms: 3 + X = 5(-5 + 2x) 3 + X = (-5 * 5 + 2x * 5) 3 + X = (-25 + 10x) Solving 3 + X = -25 + 10x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + X = -25 + -3 + 10x Combine like terms: 3 + -3 = 0 0 + X = -25 + -3 + 10x X = -25 + -3 + 10x Combine like terms: -25 + -3 = -28 X = -28 + 10x Simplifying X = -28 + 10x
| X^2-34=-34 | | 3a^2-26a+9=0 | | 4x^2-4x+10=0 | | X^2+13=-12 | | x^3+y^3=4 | | -18-6g=6+18g | | 9xy-9=3x+2 | | X^2+17=66 | | 200m-100m+48000=50500-150m | | 5x+11=29-3x | | 7a-10=11 | | -7(x-15.6)=9 | | 16=2n+10 | | (3x-3)=(2x+13) | | -6(-3y+3)-6y=2(y-9)-5 | | 2=2b-16 | | 2=3(x-1)+4-2x | | -2=-(t-8) | | 15x^4-35x^2=0 | | 7a(a+5)-(a+5)=0 | | -7x+25+9x+25=-4 | | 10e+1h+0.125x=100 | | 10=2w+6 | | z^3-5z^2+2z+10=0 | | 5*n+5j=z | | 2+7n=-2+7n | | 2x+11=900 | | 3x(x-5)=6x^2-16 | | 7a-2+3=8 | | 5n+5j=z | | 3(b-2)+5=9 | | 4a+3b=6b-9b |